2008
DOI: 10.1002/hbm.20635
|View full text |Cite
|
Sign up to set email alerts
|

fMRI evidence for multisensory recruitment associated with rapid eye movements during sleep

Abstract: We studied the neural correlates of rapid eye movement during sleep (REM) by timing REMs from video recording and using rapid event-related functional MRI. Consistent with the hypothesis that REMs share the brain systems and mechanisms with waking eye movements and are visually-targeted saccades, we found REM-locked activation in the primary visual cortex, thalamic reticular nucleus (TRN), ‘visual claustrum’, retrosplenial cortex (RSC, only on the right hemisphere), fusiform gyrus, anterior cingulate cortex, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
153
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(167 citation statements)
references
References 63 publications
13
153
0
1
Order By: Relevance
“…However, REMS visual imagery uses very similar neural systems as those used in wakefulness (Borst, & Kosslyn, 2010Sprenger et al, 2010. Nevertheless, recent event-related fMRI showed activation of V1 during REMS (Hong et al, 2009Miyauchi et al, 2009) and the findings that REMS associated visual imagery uses very similar neural systems as those used in wakefulness (Nir & Tononi, 2010Sprenger et al, 2010 support our contention.…”
Section: Activation Of Retinotopic V1 Area During Visual Imagery and supporting
confidence: 72%
See 4 more Smart Citations
“…However, REMS visual imagery uses very similar neural systems as those used in wakefulness (Borst, & Kosslyn, 2010Sprenger et al, 2010. Nevertheless, recent event-related fMRI showed activation of V1 during REMS (Hong et al, 2009Miyauchi et al, 2009) and the findings that REMS associated visual imagery uses very similar neural systems as those used in wakefulness (Nir & Tononi, 2010Sprenger et al, 2010 support our contention.…”
Section: Activation Of Retinotopic V1 Area During Visual Imagery and supporting
confidence: 72%
“…Recently, Hong et al (2009) confirmed the REM-locked activation in the striate cortices. According to Hong et al (2009) (Kosslyn, 1994, p. 75).…”
Section: The Eyes Scan Dream Images During Remsmentioning
confidence: 81%
See 3 more Smart Citations